ANALISIS KINERJA KEUANGAN PT. PERKEBUNAN NUSANTARA XIV (PERSERO) UNIT LUWU - St Hadijah, Andi; Surianto, Surianto (Paser Institute Of Accounting and Finance, 2023)
This study aims to analyze the financial performance of PT. Perkebunan Nusantara XIV (Persero), Luwu unit, using descriptive analysis through financial ratios. The objective of this analysis is to evaluate the financial health of the company and identify trends that have occurred over the past five years. The method of analysis employed is descriptive analysis with a focus on relevant financial ratios. Financial ratios measured include but are not limited to profitability, liquidity, solvency, and activity ratios. Financial ratio analysis provides a comprehensive overview of the company's financial performance and enables a better understanding of its financial situation. The results of the study indicate that the financial performance of PT. Perkebunan Nusantara XIV (Persero), Luwu unit, over the past five years has experienced fluctuations. These fluctuations may be caused by various external and internal factors affecting the company's operations and financial results. Further interpretation of the results of this financial ratio analysis can provide deeper insights into the factors influencing the company's financial performance as well as recommendations for necessary improvements.